Pengaruh Model Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, and Review) terhadap Kemampuan Menganalisis Unsur Naskah Drama Siswa Kelas XI SMA Negeri 3 Lubuklinggau - Sartika, Wila; Effendi, M. Syahrun (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to determine the effect of the PQ4R model (Preview, Question, Read, Reflect, Recite, and Review) on the ability to analyze the drama script elements of class XI students of SMA Negeri 3 Lubuklinggau. This research method is an experimental method. The population of class XI students is 258 students consisting of 8 classes. The sampling technique uses simple random sampling technique and the research sample is class XI IPA 1 totaling 30 students and class XI IPA 2 totaling 30 students. Data collection using test techniques. Data were analyzed using the "t" test formula. Based on the results of data analysis, furthermore, thit was consulted with ttab on the t distribution list with a significant level of 5%. Because dk = 58 is not found in the table, the writer uses the value of ttab with dk = 60. At the 5% confidence level is 2.00. Thus, thit: 2.79> ttab: 2.00. Thus, it can be concluded that the PQ4R Model can have an influence on the ability to analyze the elements of drama script for grade XI students of SMA Negeri 3 Lubuklinggau.